Yeast breads from two levels of sweet potato-wheat flour composite - Hans, Rosa J. (1981)
ABSTRACT The study was undertaken to determine the effect on bread quality of diluting wheat flour with sweet potato flour. The study was divided into two phases: Phase I involved establishing the effects on the loaf bread of mixing sweet potato flour at two levels with wheat flour. The levels used were 20:80 and 40:60 of sweet potato flour to wheat flour. It was found that the specific volume of loaf bread decreased as the level of sweet potato flour was increased. Correspondingly, the bread containing the higher level of sweet potato flour was the densest among the three experimental breads. The evaluation of sensory attributes indicated no significant differences in flavor, crumb texture, and general acceptability but significant differences in contour, crust texture and crumb color of the breads. In Phase II, the effects of the addition of Cremodan, an emulsifier, at two concentrations, 0.20% and 0.50% based on flour weight, to the 20:80 and 40:60 composite flour dough was determined. The results showed that as the concentration of Cremodan was increased, the specific volume increased with no resulting significant difference in the sensory qualities among the experimental breads.